Chemokines And Growth Factors As Key Mediators Of Immunoangiogenic Mechanisms In Uterine Fibroids (Review Paper) (Texas Journal of Medical Science, 2025)
This review systematizes current data on the role of chemokines (CXCL8, CXCL10, CCL2, CCL3, CCL4, CCL5) and growth factors (VEGF-A, TGF-β1/β2, EGF, FGF2) in the immuno-inflammatory and angiogenic mechanisms underlying the pathogenesis of uterine fibroids. It is shown that elevated levels of these mediators promote the activation of macrophages, T-lymphocytes, and endothelial cells, thereby enhancing angiogenesis and stromal fibrosis. The imbalance between pro-inflammatory and angiostatic cytokines forms a microenvironment that supports the growth and recurrence of fibroid nodules. The summarized data confirm the pivotal role of chemokines and growth factors as pathogenetic determinants and potential biomarkers of leiomyoma activity, opening new prospects for the development of targeted and immunotherapeutic strategies in gynecology